TNF Receptor: Fc Fusion Protein Downregulates RANKL/OPG Ratio by Inhibiting CXCL16/CXCR6 in Active Ankylosing Spondylitis - Zhang, Peiyi; Zhou, Shufen; Chen, Zhe; Tian, Ye; Wang, Qianqian; Li, Hui; Zhang, Tiantian; Guo, Qin; Wang, Meiying; Guo, Chengshan (Current Pharmaceutical Biotechnology, 2021)
Background: Clinical studies indicate that recombinant tumor necrosis factor receptor:Fc fusion protein (rhTNFR:Fc) quickly alleviates symptoms and physical signs of active Ankylosing Spondylitis (AS), improving the manifestation of spinal inflammation on radiological imaging. However, the regulatory mechanism of rhTNFR:Fc in the chemokine pathway is unclear. Thus we study the mechanism of phlogogenic activity of CXCL16/CXCR6 in AS and the related mechanism of rhTNFR: Fc treatment. Methods: Thirty-two cases of active AS were treated with rhTNFR:Fc for 3 consecutive months. Clinical response was evaluated at baseline and after treatment. CXCL16/CXCR6 expression as well as Receptor Activator Of Nuclear Factor-b Ligand (RANKL)/Osteoprotegerin (OPG), essential molecules for osteoclast differentiation, were studied in AS before and after treatment. Further, the proliferation of lymphocytes and the RANKL level stimulated by recombinant human CXCL16 (rhCXCL16) were measured in vitro. Results: Thirty cases responded to rhTNFR:Fc treatment. The RANKL level, RANKL/OPG ratio, CXCLl6 level in serum, and CXCLl6 and CXCR6 mRNA levels in active AS were higher than those in controls and treated patients (P<0.001). rhCXCL16 treatment increased lymphocyte proliferation and RANKL level in active AS (P<0.001), but not in controls or treated patients (P>0.05). A positive linear correlation was noted between CXCL16 serum levels and RANKL/OPG ratio and between CXCL16 levels and C-reactive protein results (P<0.001). Conclusions: Our findings suggest that rhTNFR:Fc suppresses inflammation and bone destruction of AS by reducing the RANKL/OPG ratio through inhibition of the CXCL16/CXCR6 pathway.
Keywords: Fc fusion protein